Acetazolamide to increase natriuresis in congestive heart failure at high risk for diuretic resistance. (9th May 2019) - Verbrugge, Frederik H.; Martens, Pieter; Ameloot, Koen; Haemels, Veerle; Penders, Joris; Dupont, Matthias; Tang, Wai Hong Wilson; Droogné, Walter; Mullens, Wilfried
Abstract : Aims: To investigate the effects of acetazolamide on natriuresis, decongestion, kidney function and neurohumoral activation in acute heart failure (AHF). Methods and results: This prospective, two‐centre study included 34 AHF patients on loop diuretics with volume overload. All had a serum sodium concentration < 135 mmol/L and/or serum urea/creatinine ratio > 50 and/or an admission serum creatinine increase of > 0.3 mg/dL compared to baseline. Patients were randomised towards acetazolamide 250–500 mg daily plus bumetanide 1–2 mg bid vs. high‐dose loop diuretics (bumetanide bid with daily dose twice the oral maintenance dose). The primary endpoint was natriuresis after 24 h. Natriuresis after 24 h was similar in the combinational treatment vs. loop diuretic only arm (264 ± 126 vs. 234 ± 133 mmol; P = 0.515). Loop diuretic efficiency, defined as natriuresis corrected for loop diuretic dose, was higher in the group receiving acetazolamide (84 ± 46 vs. 52 ± 42 mmol/mg bumetanide; P = 0.048). More patients in the combinational treatment arm had an increase in serum creatinine levels > 0.3 mg/dL ( P = 0.046). N‐terminal pro‐B‐type natriuretic peptide reduction and peak neurohumoral activation within 72 h were comparable among treatment arms. There was a non‐significant trend towards lower all‐cause mortality or heart failure readmissions in the group receiving acetazolamide with low‐dose loop diuretics vs. high‐dose loop diuretic monotherapy ( P = 0.098). Conclusion: Addition of acetazolamide increases the natriuretic response to loop diuretics compared to an increase in loop diuretic dose in AHF at high risk for diuretic resistance. Trial registration: ClinicalTrials.gov NCT01973335.